In vitro antibiotic susceptibility testing of clinical isolates of Mycoplasma penetrans from patients with AIDS. - Hayes, M M (1995)
In vitro susceptibilities of Mycoplasma penetrans were determined. MICs and MBCs were determined. The MICs at which 50% of the isolates are inhibited (micrograms per milliliter) for broth dilution testing were as follows: azithromycin, 0.039; chloramphenicol, 0.625; ciprofloxacin, 0.156; clindamycin, 0.078; doxycycline, 0.312; erythromycin, 0.312; gentamicin. > 10; levofloxacin, 0.078; lincomycin, 0.625; streptomycin, > 10; and tetracycline, 1.25. Bactericidal activity was significant only for ciprofloxacin (MBC at which 50% of the isolates are killed, 0.312 microgram/ml) and levofloxacin (MBC at which 50% of the isolates are killed, 0.312 microgram/ml).